Pengaruh Harga dan Kualitas Produk Terhadap Loyalitas Pelanggan Dengan Perceived value Sebagai Variabel Mediasi (Studi Pada Pelanggan PT Digital Media Telematika) - Kofifa Zunia Lestari; M Adhitya Nugraha Pratama; Qudwatun Niswah; Muhammad Sulton (CV. ITTC INDONESIA, 2026)
The swift progress of information technology in Indonesia has shifted the Internet from a simple communication medium to an essential pillar for economic endeavors, learning, and social connections. This shift has heightened rivalry among Internet Service Providers, underscoring the critical role of customer loyalty in ensuring sustained business viability. This research investigates the factors influencing customer loyalty at PT Digital Media Telematics by exploring the impacts of product quality and pricing, with perceived value acting as a mediating factor. A quantitative method was utilized, gathering data from 95 customers via a structured questionnaire on a five-point Likert scale. The data underwent analysis through partial least squares structural equation modeling to evaluate both direct and indirect links between variables. Findings reveal that product quality exerts a direct and significant effect on customer loyalty, emphasizing the value of dependable performance and steady service standards. Conversely, pricing does not impact loyalty directly but does so indirectly via perceived value. Perceived value is pivotal in converting customers' assessments of costs and service advantages into enduring dedication. Customers perceiving greater functional, emotional, and social value are more inclined to stay loyal, keep using the service, and endorse it to others. Overall implications.